CONSEQUENCE OF INSURGENCY ON THE LIVELIHOOD OF MICHIKA, ADAMAWA STATE, NIGERIA - Vulegbo, Umar Haliru; Umaru, Kuso; Yakatun, Musa Mohammed; Makun, Ahmed Isah (FUDMA JOURNAL OF SCIENCES, 2025)
Insurgency has become a pervasive threat to global peace and security, with devastating consequences on the livelihoods of affected communities. This study examines the consequences of insurgency on the livelihoods of households in Michika, Adamawa State, Nigeria. Using a mixed-methods approach, the study reveals that the insurgency has had a devastating impact on agricultural productivity, income generation, and food security among households in Michika. A total of 300 households were sampled using stratified random sampling technique. The study also explores the coping mechanisms adopted by households to mitigate the effects of insurgency on their livelihoods. The findings of the study highlight the need for urgent intervention to address the humanitarian crisis in Michika, including the provision of food aid, farm inputs, and support for affected businesses. The study recommends the implementation of policies and programs to reintegrate internally displaced persons into their lost socioeconomic activities, as well as the establishment of community policing and intelligent sharing initiatives to prevent future security breaches.